Pendidikan Islam Sebagai Proses Transformasi Sosial - syahrudin (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
Abstract Critical education is basically a school of thought in education for empowerment and liberation. The basic foundation of the critical education tradition is the ideological critique of thought and paradigm of unfair social, economic and political systems and structures. Thus education in this perspective is a medium for resistance and social action that cannot be separated and is part of the process of social transformation. So critical education is a process of political struggle of the oppressed.A reality does not have to be a must. If reality deviates from necessity, then it is the duty of man to change it, to suit what it should be. The reality is often called nature. True human nature is the doer (subject), not the object or sufferer. Human nature is to be free and be free. All of these are often referred to as Freire's goal of humanization. The essence of education is to raise critical awareness as a prerequisite for the process of humanization or humanizing humans. The key to this educational process is conscientization or the process of generating critical awareness.Change basically comes from three sources, namely First, the adjustment of the system to external changes (extra-systemic). Second, changes in structure and differentiation of functions and Third, new findings and innovations of group members in society. The most basic factor for integration to occur is the existence of consensus values, namely the overall basic structure and culture. Thus the transformation process is a process of creating something new produced by science and technology (tools and technologies), what changes is the cultural aspect which is material in nature, while the norm and it is very difficult to make changes (there are even propensity to maintain). Islamic education has elements of universality (as seen in the basic concept of rahmatan lil 'alamin), emancipation and egalitarianism. Islam describes a view that covers all aspects of life in addition to paying attention to social problems. Islam is also a school of thought that guarantees human life both individually and in groups and its mission is to guide the future of mankind. The critical role of Islam should be internalized in the concept of Islamic education. That is, Islamic education must be able to become a liberating instrument and as a catalyst in the process of social transformation